Information modeling of earthquake-damaged reinforced concrete structures. Issue 3 (August 2015) - Ma, Ling; Sacks, Rafael; Zeibak-Shini, Reem
Abstract Accurate and reliable information about buildings can greatly improve post-earthquake responses, such as search and rescue, repair and recovery. Building Information Modeling (BIM), rapid scanning and other assessment technologies offer the opportunity not only to retrieve as-built information but also to compile as-damaged models. This research proposes an information model to facilitate the data flow for post-earthquake assessment of reinforced concrete structures. The schema development was based on typical damage modes and the existing Industry Foundation Class (IFC) schema. Two examples of damaged structures from recent earthquake events, compiled using an experimental damage modeling software, illustrate the use of the data model. The model introduces two new classes, one to represent segments of building elements and the other to model the relationships between segments and cracks. A unique feature is the ability to model the process of damage with a binary tree structure. Methods for exporting as-damaged instance models using IFC are also discussed.